De Urban Decision Room/The Urban Decision Room : Een Stedebouwkundig Sturingsinstrument. - Van Loon, P. P. (IOS Press, 2008)
First of all, this book is intended to give the reader a simple introduction to the Urban Decision Room (UDR) system in definitions and diagrams. Second, it demonstrates the model-based construction of the system in terms of urban planning. Third, it focu.